Laser meridian massage decreased craving in men with opioid use disorder on methadone maintenance treatment - Wen-Long Hu; Meng-Chang Tsai; Chun-En Kuo; Chun-Ting Liu; Szu-Ying Wu; Tzu-Chan Wu; Yu-Chiang Hung (Biomedical Journal, 2022)
Background: The incidence of opioid use disorder (OUD) is increasing worldwide, and the opioid-related overdose crisis is currently a major global challenge. This study investigated the effects of adjuvant laser meridian massage (LMM) in men with OUD undergoing methadone maintenance treatment (MMT). Methods: A case-controlled study was conducted from February 2019 to April 2020. Fourteen men with OUD on MMT were enrolled from an addiction treatment center as an experimental group. An age-matched control group comprising 13 men was also enrolled. The experimental group received LMM on the back, including over the Bladder meridian and Governor Vessel, three times weekly for 4 weeks. The control group received only MMT. Urinary morphine levels, patients’ self-reports of the number of episodes or days of heroin use, and visual analog scale scores for heroin craving/refusal to use heroin during the previous week were evaluated. Quality of life was reported using the Short Form (SF)-12v2. Results: The experimental group showed a significant decrease in heroin use (p < 0.05), whereas the control group showed a significant increase in heroin craving (p < 0.05). The SF-12v2 Health Survey revealed a significant improvement in physical health in the experimental group (P < 0.05). Conclusion: The results of this study suggest that laser meridian massage can be considered a safe, well-tolerated, and potentially useful adjuvant intervention for opioid use disorder.